Wheat gluten-stabilized high internal phase emulsions as mayonnaise replacers. (April 2018) - Liu, Xiao; Guo, Jian; Wan, Zhi-Li; Liu, Yu-Yang; Ruan, Qi-Jun; Yang, Xiao-Quan
Abstract: Plant protein-based diets (e.g., egg or meat alternatives) have emerged as a promising approach for developing healthy and sustainable food systems. Mayonnaise, a formulated sauce prepared by mixing vegetable oil, egg yolk, vinegar and salt, is probably one of the most widely used condiments in the world today. In this paper, wheat gluten (WG) as an available and low-cost plant protein ingredient was used to prepare and stabilize oil-in-water high internal phase emulsions (HIPEs) as mayonnaise replacers via emulsification–evaporation method. Firstly, WG was dissolved into aqueous acetic acid/ethanol (55/45, v/v, pH 3.0) solution to form phase-separated WG particles, and then HIPEs were prepared through homogenization of high sunflower oil fraction (75 wt%) with WG particles suspension at 80 °C after evaporating ethanol completely. Compared with egg-based mayonnaise, HIPEs (especially for 1.0 wt% WG) exhibited very similar droplet size distribution, rheological behavior, near-perfect thixotropic recovery, and tribological property. These results demonstrated that HIPEs and mayonnaise might have similar sensory property and perceived texture such as creaminess, smoothness, and sliminess. The confocal laser scanning microscopy (CLSM) indicated that close-packed oil droplets could allow them to form homogeneous oil-in-protein network microstructure in HIPEs and mayonnaise, which might contribute to high viscoelasticity, consistency, and correct texture. In addition, thermal stability of HIPEs was much better than that of the mayonnaise. Design and construction of WG-stabilized oil-in-water HIPEs may provide a potential strategy for preparing mayonnaise replacers. Graphical abstract: Image 1 Highlights: Wheat gluten (WG)-stabilized oil-in-water high internal phase emulsions (HIPEs) as mayonnaise replacers were prepared via emulsification–evaporation strategy. HIPEs and mayonnaise exhibited very similar droplet size distribution, rheological behavior, near-perfect thixotropic recovery, and tribological property. Formation of homogeneous oil-in-protein network microstructure in HIPEs and mayonnaise.